PERAN DINAS PERHUBUNGAN DALAM PERIZINAN ANGKUTAN JALAN (Studi Kasus Angkutan Becak Motor di Kota Dumai Tahun 2012) - DERI SATRIA MUKTI; Hery Suryadi (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2014)
problems that occur on public transport or transport in the city is dumai emergence of a phenomenon occurs where motor tricycles mushroomed in the dumai city and has become one of people’s livelihood, whose whereabouts are still not getting the attention and recognition as one of the government’s official transportation. Although the application of motor tricycles in the city late dumai from other big cities and make a polemic with the paddle rickshaw due to the very tight competition, so the paddle rickshaw abandoned by users of transport services and also give rise to protests from other transportation is public transportation. While operating a motor tricyles permit has not been issued operational. But with the presence of motor tricycles become one of the excellent transport alternatives help the people in the town dumai activity with low rates and fast, so that people can reach their destination make motor tricycles have a fairly high competitiveness in providing transportation services to the community.Therefore it must needs be a clear regulation to adjust the motor tricycles, so that the problem can be minimized. Department of transportation as well as the role of government in charge of the transport sector in collaboration with the police should immediately find a solution to overcome this motor tricycles.Keyword : Department of transportation, public transport, motor tricycle